A study of the effect of palatal and labial anesthesia on stuttering - Devaraj N (Journal of All India Institute of Speech and Hearing, 1970)
Problem of the study was to note the role of tactile and kinesthetic feedbacks from palate and lips in stuttering. One way of studying this is by disturbing the feedback. This was done by anesthetization of palate and lips separately.